2014
DOI: 10.1074/jbc.m114.608547
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the Human Fatty Acid Synthase Enoyl-Acyl Carrier Protein-Reductase Domain Complexed with Triclosan Reveals Allosteric Protein-Protein Interface Inhibition

Abstract: Background: Enoyl reductase (hER) is a catalytic domain in cancer-associated human fatty acid synthase (FAS) and is inhibited by triclosan. Results: Triclosan binds at the protein-protein interface (PPI), causing distant active site changes. Conclusion: Triclosan is an allosteric PPI inhibitor. Significance: Triclosan can be used to develop PPI FAS inhibitors for anti-cancer therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 61 publications
0
12
0
1
Order By: Relevance
“…For mFAS, the structural model of the core elongation domains has enabled rational dissection into crystallizable fragments 39, 40, 135 . These fragments have successfully been employed in screening small-molecule FAS inhibitors as potential leads against cancer and metabolic disorders.…”
Section: Resultsmentioning
confidence: 99%
“…For mFAS, the structural model of the core elongation domains has enabled rational dissection into crystallizable fragments 39, 40, 135 . These fragments have successfully been employed in screening small-molecule FAS inhibitors as potential leads against cancer and metabolic disorders.…”
Section: Resultsmentioning
confidence: 99%
“…In 2002 triclosan was reported to inhibit the ER domain of FASN and as a result, demonstrated cytotoxicity in BC cell lines (Liu et al, ). A recent protein crystal structure revealed that inhibition of FASN by triclosan occurs by allosteric binding at a protein‐protein interface of the ER domain, rather than binding at the active site (Sippel et al, ).…”
Section: Oncogenic Antigen 519mentioning
confidence: 99%
“…Other countries, including the members of European Union, have banned or restricted use of this biocide in certain consumer products [ 19 ]. In addition, recent reports suggest that TCS is a potential endocrine disrupter [ 20 ], inhibitor of various important enzymes of the human body [ 21 – 22 ], elicitor of skin and pulmonary allergies [ 23 – 24 ] and occupational asthma [ 25 ]. TCS can potentially alter the microbiome of newborns [ 26 ] and was reported to enrich the gut bacterial genes related to TCS and other antibiotic resistance [ 27 ].…”
Section: Introductionmentioning
confidence: 99%